Patient's Subjective Impression of Cervical Range of Motion: A Mixed-methods Approach. Issue 18 (15th September 2018) - Langenfeld, Anke; Bastiaenen, Carolien; Sieben, Judith; Humphreys, B. Kim; Swanenburg, Jaap
Abstract : Study Design: Mixed-method. Objective: To evaluate the association between objective and subjective cervical range of motion (ROM) among patients with neck pain, and to assess the awareness of impairments. Summary of Background Data: Cervical ROM is frequently used to evaluate neck pain, but it is also important to know what a patient expects from treatment, because this can profoundly affect treatment outcomes and patient satisfaction. Methods: We used a cervical ROM instrument, the Neck Disability Index (NDI), and a self-administered ROM questionnaire for the neck (S-ROM-Neck). Ten patients took part in semi-structured interviews. Correlations were analyzed using Spearman rank order correlations (rs ). Differences between patient and assessor were evaluated by the Mann-Whitney U test. Qualitative data were analyzed by content analysis. Results: Thirty participants (mean age 43.80 years; 21 females) were included. The correlation (rs ) for the S-ROM-Neck between patient and assessor was 0.679 [95% confidence interval (95% CI) 0.404–0.884; P = 0.000]. The correlation between the NDI and S-ROM-Neck was 0.178 (95% CI −0.233 to -0.533; P = 346) for the assessor and −0.116 (95% CI −0.475 to −0.219, P = 0.541) for the patient ( U = 448, z = −0.030, P = 0.976). Qualitative analysis revealed that patients had general restrictions in daily life and with specific movements, but that they adjusted their behavior to avoid impairment. Conclusion: There was a significant correlation between patient and therapist ratings of cervical spine mobility. Although patients experience restriction while moving and are impaired in specific activities, they adjust their lifestyle to accommodate their limitations. Level of Evidence: 4